Dissolution enhancement of leflunomide incorporating self emulsifying drug delivery systems and liquisolid concepts - Nihal M. El-Ma; Alia Badawi; Mohammed Effat Abdullah; Nevine Shawky Abdelmalak (Faculty of Pharmacy, Cairo University, 2017)
The objective of this study is to enhance the dissolution properties of leflunomide, a class BCS-II drug by incorporating the self emulsifying (SE) form of the drug onto liquisolid systems in the form of tablets. Different formulae were prepared by dissolving leflunomide in PEG300 then forming SE systems using tween 80 as surfactant and either sesame oil and paraffin oil then adsorbing on powder excipients to form SE liquisolid powders. The prepared powders showed adequate flowability. The drug and excipients showed compatibility by analysis with DSC, XRD and FTIR. After compression, all tablets showed adequate weight variation, friability and disintegration time with disintegration time ranging between 8.45 ± 0.16 min and 10.7 ± 0.29 min. All liquisolid tablets exhibited higher in vitro dissolution in distilled water compared to physical mixture and the commercial tablets (Arthfree®) with formula containing sesame oil and highest amount of solvent (TS04) exhibiting the highest dissolution profile and it did not change by the change in the pH of the dissolution medium. The tablets showed stability during a 6 months accelerated stability study according to appearance, drug content, disintegration time and dissolution profile. Thus it can be concluded that combining self emulsifying drug delivery technique and liquisolid technology can be a promising tool to enhance the dissolution profile of leflunomide in vitro.